1988
DOI: 10.1002/mus.880110608
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potentials: Lack of value for diagnosis of thoracic outlet syndrome

Abstract: Twenty patients with thoracic outlet syndrome (TOS) seen at the Mayo Clinic between October 1984 and November 1985 were studied prospectively with routine nerve conduction studies, concentric needle examination, and bilateral median and ulnar somatosensory evoked potentials (SEPs). Results of nerve conduction studies and needle examination were abnormal in 30% of the patients, one patient having a reduced ulnar sensory nerve action potential amplitude and five others having neurogenic motor unit potential chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…There are reports of a focal proximal slowing by stimulating at Erb's point and recording at the hypothenar muscles. 1,13,14 However, the reliability of these reports has been questioned. 2,4,16 Direct needle stimulation of the C8 root and surface stimulation in the supraclavicular fossa have been used to measure conduction across the thoracic outlet.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are reports of a focal proximal slowing by stimulating at Erb's point and recording at the hypothenar muscles. 1,13,14 However, the reliability of these reports has been questioned. 2,4,16 Direct needle stimulation of the C8 root and surface stimulation in the supraclavicular fossa have been used to measure conduction across the thoracic outlet.…”
Section: Discussionmentioning
confidence: 94%
“…12 The use of somatosensory evoked potentials for diagnostic purposes has also been questioned. 14,22 Our 6 patients had clinical features typical of true neurogenic TOS. All were female and presented marked atrophy of the thenar muscles.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in the case of positive results, F-wave may not be useful in narrowing the differential or localizing the lesion as the causative fiber loss may be expected in patients with severe denervation, regardless of the etiology. [43][44][45] Somatosensory evoked potentials studies have been found useful in some reports. 46,47 However, somatosensory evoked potential has also been criticized as nonspecific, nonlocalizing, and rarely abnormal.…”
Section: Electrodiagnostic Studiesmentioning
confidence: 97%
“…The ulnar NCS reported as useful in TOS 84 has been shown to be of no value, 87 as have other techniques designed to assess this segment of the peripheral nervous system. 85 Symptomatic TOS remains as a clinical diagnosis.…”
Section: Electrodiagnostic Evaluation In Performersmentioning
confidence: 99%